İstanbul Boğazı yüzey sedimentlerinde ağır metal birikiminin incelenmesi - Burgaç, Ahmet (My University, 2014)
İstanbul Boğazı dünyanın önemli su geçiş yolları arasındadır. Asya ve Avrupa kıtalarını ayıran bir su yolu olması, dünyanın kapalı denizlerinden biri olan Karadeniz’in diğer denizlerle bağlantısını sağlayan boğaz olması ve ülkemizin nüfus, sanayi, ticaretbakımından en büyük merkezi olan İstanbul sınırları içerisinde yer alması İstanbul Boğazının önemini ortaya koymaktadır. İstanbul Boğazı’nın bu özellikleri aynı zamanda kendisi için bir kirlilik riski oluşturmaktadır. Bu çalışmada: İstanbul Boğazından 15 ayrı noktadan yüzey sediment örnekleri alınarak X-ışınları Fluoresans (XRF) spektrometresinde metal içerikleri saptanmıştır. Yüzey sediment örneklerinde yapılan analiz sonuçlarına göre; As elementi 5,3-26,5 mg/ kg, Zn elementi 37,4-277,1 mg/ kg, Pb elementi bdl-50,3 mg/ kg, Cr elementi 42,2-150,0 mg/ kg, Cu elementi 12,9-114,2 mg/ kg, Ni bdl-155,0 mg/ kg, Sn elementi bdl-42,6 mg/ kg, Cd elementi 0,95-1,4 mg/ kg arasında bulunmuşlardır. Sedimentteki metal kirliliğini değerlendirmek için 2 metot kullanılmıştır. Sediment kalitesi guidlinesi (SQG) (National Oceanographic and Atmospheric Admnistration (NOAA) tarafından geliştirilmiştir), geobirikim endeksi (IGEO). SQG yöntemi ile kıyısal sedimentlerdeki metal konsantrasyonların olumsuz biyolojik etkilerinin saptanması için kullanılmıştır. Bentik organizmalara etkisini belirlemek amacıyla üst guidline değerlerini geçen elementlerin (effects range medium, ERM) ve alt gudline değerleri (effects range lower,ERL) hesaplanmıştır. NOAA değerlerine göre Ni biyolojik yapıya en çok etki eden kontaminanttır. Geobirikim endeksine göre (IGEO) As ve Cd, kontaminant olarak tüm çalışma alanında bulunmaktadır. stanbul Boğazı, Ağır metaller, Sediment, X-ışınları Fluoresans (XRF) ABSTRACTThe Bosphorus ranks highly as one of the most important water straits in the world,because of its unique position that separates the two continents of Europe and Asia and being the singular opening gateway of the Black Sea. Furthermore, it is situated directly within the city borders of Istanbul metropolitan area which happens to be the highest populated city as well as the industry and commerce center of Turkey. Also holding the position of being the only passage way between the two interior seas of the Marmara and the Black Sea, the Bosphorus nowadays is facing environmental pollution risk due to the industrial plants situated on the coast of Marmara and pollution carried from the other countries around the Black Sea coast. This study: Surficial sediments from 15 stations in the Istanbul Strait were collected and analyzed for metal contents by X-ray fluorescence (XRF). Metal concentrations in surface sediments varied from 5,3 to 26,5 mg/ kg for As, 37,4 to 277,1 mg/ kg for Zn, bdl to 50,25 mg/ kg for, 42,2 to 150,5 mg/ kg for Cr, 12,9 to 114,2 mg/ kg for Cu, bdl for 155,1 for Ni, bdl to 42,6 mg/ kg for Sn, 0,95 to 1,4 mg/ kg for Cd. Two tools have been applied in order to evaluate metal pollution in the Bosphorus sediments; Sediment quality guidelines (SQGs), developed by the National Oceanographic and Atmospheric Administration (NOAA), and geoaccumulation index (Igeo). NOAA, SQGs are used to estimate possible adverse biological effects of metals in the coastal sediments of Istanbul Strait to benthic animals by determining the samples exceeding an upper guideline value (effects range medium, or ERM) and lower guideline value (effects range lower, or ERL). The NOAA values indicate that Ni is the most likely contaminant to cause adverse biological effects. On the other hand, geoaccumulation index (Igeo) shows that As and Cd contamination exists in the entire. The Strait of Istanbul, heavy metal, sediment, X-ray fluorescence (XRF) spectrometers
Keywords: Ağır metaller; Boğazı; Çevresel etkisi; Deniz kirliliği; heavy metal; İst; İstanbu Boğazı (Türkiye); Sediment; Su ürünleri; Türkiye; XRF; XRF The Strait of Ist